Framework-Shrinkage-Induced Wavelength-Switchable Lasing from a Single Hydrogen-Bonded Organic Framework Microcrystal - Lv, Yuanchao; Xiong, Zhile; Li, Yunbin; Li, Delin; Liang, Jiashuai; Yang, Yisi; Xiang, Fahui; Xiang, Shengchang; Zhao, Yong Sheng; Zhang, Zhangjing (The journal of physical chemistry letters, 2022)
Porous organic materials (POMs) have shown great potential for fabricating tunable miniaturized lasers. However, most pure-POM micro/nanolasers are achieved via coordination interactions, during which strong charge exchanges inevitably destroy the intrinsic gain property and even lead to optical quenching, hindering their practical applications. Herein, we reported on an approach to realize hydrogen-bonded organic framework (HOF)-based in situ wavelength-switchable lasing based on the framework-shrinkage effect. A flexible HOF with reversible framework shrinkage was constructed from gain blocks with multiple rotors. The framework shrinkage of the HOF induced the in situ regulation on the conformation and conjugation degree of gain blocks, leading to distinct energy-level structures with blue/green-color gain emissions. Inspired by this, the in situ wavelength-switchable lasing from HOF microcrystals was achieved through reversibly controlling the framework shrinkage via the absorption/desorption of guests. The results offer useful insight into the use of flexible HOFs for exploiting miniaturized lasers with on-demand nanophotonics performance.